Inspecting VANET with Various Critical Aspects - A Systematic Review - Karabulut, Muhammet Ali; Shah, A. F. M. Shahen; Ilhan, Haci; Pathan, Al-Sakib Khan; Atiquzzaman, Mohammed (ELSEVIER, 2023)
Due to its strategic significance in the area of smart transportation to facilitate Vehicle-to-Vehicle (V2V) and Vehicle-to-Infrastructure (V2I) communication, Vehicular Ad Hoc Networks (VANETs) have grown very popular in recent years. The rapid increase in the number of vehicles on the road has also led to the development of heterogeneous, large-scale, and highly dynamic VANETs, which introduce difficulty to fulfill the stringent requirements, which include low latency, high mobility, top security, and massive connectivity of the 5G network. Research works in VANETs mainly focus on message transmission within strict delay requirements based on different applications, data privacy and security. In this respect, a number of studies have been carried out by the researchers that propose models and solutions linked to the enhancement of VANET from several aspects, including applications, Quality of Service (QoS), security, physical layer fading, Artificial Intelligence (AI) techniques, Medium Access Control (MAC), and routing protocols. These factors serve as the driving force for this study's thorough examination of VANETs, which includes information on specific applications, QoS, channel fading, MAC protocols, channel access mechanisms, routing protocols, security, and difficulties. None of the surveys in existence today address all critical aspects of VANET in a single survey. In this paper, a complete taxonomy of VANETs has been provided based on various issues. First, an overview of VANET is presented with different applications. Then, QoS in VANETs and different proposed MAC protocols are discussed. Channel fading and access mechanisms are presented. After that, routing protocols, security, and clustering in VANETs are provided. AI approaches proposed in VANET are also summarized. Finally, a discussion of future research direction for all aspects is presented. This article might be used as a guide or a point of reference while designing and creating applications, networking and communication systems, and data security for VANETs.
Keywords: AI; channel fading; MAC protocols; routing protocols; security; VANETs; MULTICHANNEL MAC PROTOCOLS; CLUSTERING-ALGORITHM; COMPREHENSIVE SURVEY; SECURITY CHALLENGES; ADHOC MAC; PERFORMANCE; OPTIMIZATION; MODELS; SAFETY; Computer Science; Telecommunications